Peningkatan Literasi pada Anak Usia Dini di Sekolah Dasar Negeri 1 Pombeyoha - Muh. Kevin Mufhly (Yayasan Daarul Huda Kruengmane, 2026)
The development of literacy skills in early childhood is the primary foundation for subsequent educational success. Literacy is not simply the ability to read and write, but also the ability to understand meaning, think critically, and express oneself. During the early years (0–6 years), children's brains develop rapidly, making it the golden age for instilling literacy habits. However, the reality on the ground shows that early childhood reading interest remains low. Many children are more interested in gadgets than books. This requires the active role of teachers and parents in fostering a culture of literacy through enjoyable activities that are developmentally appropriate.